AN ANALYSIS OF STUDENTS’ INTONATION ABILITY IN READING ENGLISH SHORT STORY TEXT - Sari, Nila Fadhilah; ', Hadriana; ', Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was descriptive analysis research. There were one variable used in this research. The variable X was the students? intonation ability in reading English story text. The subject of this research was the second semester of of English Study Program at FKIP Universitas Riau Pekanbaru, while the object of this research was Intonation Ability in Reading English Story Text. The instruments used in this research were reading story text. The population of the research was 60 students. Then, in taking the sample, the writer employed random sampling technique. To find out pronunciation ability the writer used formula through Wayan and P. P. N Arientina in Kunarsih for analyzing the data. The result of this research shows that the students in pronounciation 5 sentences got 10% category in very good level, 20% category in good level, 20% category in enough level, 40% category in less level, 10% category in fail level. Based on the analysis above, the students?intonation is in enough level, because most of the students were almost in the enough level. In conclusion, the students? ability in reading English story text of English Study Program of FKIP Universitas Riau is in the level of enough.Keywords: Intonation, pronunciation, short story text